International Commodity Market Arrangement : a study of the Effects of Post-War Commodity Agreements and Compensatory Finance Schemes - Radetzki, Marian (London : C. Hurst and Co., 1970)
This is a Scrutiny of the working and effects of the tools used in various commodity agreement.
includes bibliographical references.
SJU
Loans
Keywords: International trade